Gas-liquid mass transfer studies for biomass support materials in a bioreactor - Apar, Dilek Kilic (JOHN WILEY & SONS LTD, 2010)
BACKGROUND: Oxygen mass transfer can be described and analyzed by means of the mass transfer coefficient k(L)a, which is the most important parameter involved in the design and operation of mixing-sparging equipment for bioreactors. In the present study, the effect of biomass support materials on the gas-liquid mass transfer coefficient was studied in a bioreactor under variable process conditions. The biomass support materials used were activated carbon, pumice and loofa sponge. RESULTS: Compared with the case with distilled water only, the presence of the biomass support materials negatively influenced mass transfer. On the other hand, the mass transfer coefficient increased with increased impeller speed, air flow rate and temperature; and decreased with the increase of liquid viscosity and biomass support material concentration for all cases. CONCLUSIONS: Evaluation of the experimental data showed that k(L)a values were affected by process variables. Besides the major exponential correlations used in the literature, satisfactory linear correlations for the relationship between the k(L)a and process variables were obtained. (C) 2010 Society of Chemical Industry
Keywords: gas-liquid mass transfer; bioreactor; correlation studies; activated carbon; pumice; loofa sponge; TRANSFER COEFFICIENTS; STIRRED BIOREACTORS; OXYGEN-TRANSFER; MIXING VESSELS; PARTICLES; SYSTEM; CONTACTORS; REACTORS; SOLIDS; BROTHS; Biotechnology & Applied Microbiology; Chemistry; Engineering